Product liability in comparative perspective - Fairgrieve, Duncan (Cambridge University Press, 2005)
This book examines the law in respect of financial redress for those injured by defective consumer items, known as product liability. The different approach of the courts in a variety of different countries is examined, including Western Europe, Accession Countries, North America and Japan.